Integrated Marketing Communication Based on Digital Marketing at D'emmerick Hotel Salatiga Indonesia - Annisa Khoiruni Hidaya (Publikasi Indonesia, 2024)
The aim of this research is to identify marketing communication channels used to develop social media marketing plans and appropriate implementation steps by d'Emmerick Hotel Salatiga, types and forms of content and techniques for reaching hotel customer groups through conventional and digital social media marketing channels in the most efficient way. This research is a qualitative descriptive study. The results of the analysis show that the company has used conventional and digital marketing models, especially during and after the pandemic. Digital marketing media during and after the pandemic are more widely used, including the use of: official websites, Facebook, Instagram and TikTok, while YouTube was initially used but now prefers TikTok. Apart from that, WhatsApp is also used for personal relationships. The results of the SOSTAC analysis show that there is a development in the use of social media, especially Instagram, which has a high following, which allows for a real increase in site visits